The Effect of Typological and Morphological Elements of Urban Space, And Non-Motorized Transport: The Case of Nairobi City - Mbidhi, Martin; Kibue, Susan (ICONARCH International Congress of Architecture and Planning, 2014)
At the rate the world is urbanizing, it is predicted that by 2030 all developing regions will have more people living in urban than rural areas. The rapid urbanization has led to change in urban structures leading to sprawling cities. The urban sprawl has resulted in challenges of mobility thereby making access to work opportunities and services more difficult for urban residents. The challenge for urban planners is how the urban space can be transformed innovatively to solve the mobility problem in the midst of incalculable complexity of the cities, composed as they are of so many different actors groups and institutions. This paper is based on a study conducted in Nairobi city, Kenya on Non-Motorised Transport (NMT) users. Most NMT users in Nairobi are captive to this mode of transport but are faced with long travel distance and difficult and dangerous travel environment. The study hypothesizes that the unfavourable travel environment is as a result of the poor planning and design of the urban space. It seeks to establish the effect of typo-morphological elements of the urban space on NMT travel environment by focusing on the journey to work. The study covered selected neighbourhoods in Nairobi as trip origins and the work places in the industrial area as the trip destination. A multi-stage technique was used in obtaining the primary data: interview schedule applied at trip destinations, a walk-through interview schedule applied along travel route and an observation checklist applied on four major routes selected on the basis of frequency. Preliminary results show that the spaces NMT users select to walk or cycle through are at variance with those areas designated for their use through urban planning. The study is expected to contribute towards the development and refinement of guidelines for designing new neighbourhoods and for retrofitting existing ones to better reflect current NMT planning goals. Ultimately, the predictions will be used to help determine how public resources can be best prioritized and allocated to achieve the planning goals of the city and create a safe and attractive travel environment for NMT users.